Znaczenie przezklatkowej echokardiografii w diagnostyce choroby niedokrwiennej serca = The role of transthoracic echocardiography in the diagnosis of coronary artery disease - Lenard, Rafał Marcin; Niedziela, Magdalena; Sobieszczańska, Anna; Smoleń, Agata (Journal of Education, Health and Sport, 2015)
Lenard Rafał, Niedziela Magdalena, Sobieszczańska Anna, Smoleń Agata. Znaczenie przezklatkowej echokardiografii w diagnostyce choroby niedokrwiennej serca = The role of transthoracic echocardiography in the diagnosis of coronary artery disease. Journal of Education, Health and Sport. 2015;5(11):11-24. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.33160 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A11-24 https://pbn.nauka.gov.pl/works/665723 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.09.2015. Revised 05.10.2015. Accepted: 30.10.2015. Znaczenie przezklatkowej echokardiografii w diagnostyce choroby niedokrwiennej serca The role of transthoracic echocardiography in the diagnosis of coronary artery disease Rafał Lenard1, Magdalena Niedziela2, Anna Sobieszczańska3, Agata Smoleń4 1doktorant Katedry i Zakładu Epidemiologii, Uniwersytet Medyczny w Lublinie 2Studenckie Koło Naukowe przy Katedrze i Zakładzie Epidemiologii, Uniwersytet Medyczny w Lublinie 3Katedra i Zakład Ortopedii Szczękowej Uniwersytetu Medycznego w Lublinie 4Katedra i Zakład Epidemiologii, Uniwersytet Medyczny w Lublinie 1PhD student Deparment of Epidemiology, Medical University of Lublin, Lublin, Poland 2Students Research Circle at the Deparment of Epidemiology, Medical University of Lublin, Lublin, Poland 3Department of Jaw Orthopaedics, Medical University of Lublin, Lublin, Poland 4Deparment of Epidemiology, Medical University of Lublin, Lublin, Poland Abstrakt Wprowadzenie: Zapadalność na chorobę wieńcową serca należy do najwyższych wśród chorób układu krążenia w społeczeństwach krajów wysoko rozwiniętych. Choroba niedokrwienna serca jest to zespół objawów chorobowych, które są następstwem stanu niewystarczającego zaopatrzenia komórek mięśnia serca w tlen i w substancje odżywcze, a jej obraz kliniczny wykazuje duże zróżnicowania. Jednym z cennych badań diagnostycznych w tej chorobie jest przezklatkowe badanie echokardiograficzne. Wykonywane jest w celu oceny anatomii mięśnia serca, oceny kurczliwości globalnej i odcinkowej lewej komory, oceny aorty piersiowej oraz naczyń płucnych. Cel pracy: Celem pracy była ocena znaczenia przezklatkowej echokardiografii w diagnostyce choroby niedokrwiennej serca. Skrócony opis stanu wiedzy: Wśród wielu objawów i następstw w chorobie niedokrwiennej serca może występować upośledzenie funkcji skurczowej i rozkurczowej lewej komory, niedokrwienna niedomykalność zastawki mitralnej oraz powiększenie lewego przedsionka. U pacjentów po zawale mięśnia serca, objęty niedokrwieniem obszar ulega włóknieniu i zanikowi oraz przestaje pełnić swoje funkcje. W rozpoznawaniu choroby niedokrwiennej serca ważne znaczenie ma echokardiografia obciążeniowa, zwłaszcza w przypadku współistnienia dodatkowych czynników, utrudniających interpretację próby wysiłkowej EKG. Podsumowanie: Badanie echokardiograficzne powinno być wykonywane u każdego pacjenta z podejrzeniem choroby niedokrwiennej serca. Jest ono najważniejszym badaniem w diagnostyce różnicowej bólów w klatce piersiowej i należy do badań prognostycznych u pacjentów z chorobą niedokrwienną serca. Słowa kluczowe: echokardiografia, choroba niedokrwienna serca, diagnostyka. Abstract Introduction: The incidence of coronary artery disease (CAD) is the highest of cardiovascular disease in societies of highly developed countries. Coronary artery disease is complex of clinical syndrome based on inadequate supply of heart muscle cells with oxygen and nutrients. The clinical picure of CAD shows large variation. One of the valuable diagnostic studies for this disease is transthoracic echocardiography (TTE). TTE is performed to assess the anatomy of the heart, global and segmental left ventricular contractility and the structure of the thoracic aorta and pulmonary vessels. Aim of the study The aim of the study was to evaluate the importance of transthoracic echocardiography in the diagnosis of coronary heart disease. Short description of state of knowledge Among the many symptoms and consequences of coronary artery disease impaired systolic and diastolic left ventricular contractility, ischemic mitral regurgitation and left atrial enlargement may occur. In patients after myocardial infarction, atrophy and fibrosis of myocardium is leading to impairment of myocardial function. In the diagnosis of coronary artery disease stress echocardiography is important, especially in the case of co-existing additional factors causing difficulty in the interpretation of stress ECG. Conclusion. Echocardiography should be performed in all patients with suspected coronary artery disease. It is the most important test in the differential diagnosis of chest pain. Echocardiography has a predictive value in patients with ischemic heart disease. Keywords: echocardiography, coronary artery disease, diagnosis.